Propuesta de integración del proceso de gestión de cambios de ITIL® con la metodología de administración de proyectos del Project Management Institute. - Castro-Ramírez, Manrique (Instituto Tecnológico de Costa Rica, 2011)
The Information Technology Infrastructure Library (ITIL) is the world’s most widely adopted framework by enterprises for the administration of their information systems, even when those systems are managed by a third party (Outsourcing). One of the most important processes in managing these services is the implementation of changes or modifications to the infrastructure, because since being productive systems, a failed implementation of a change may have a negative impact in the company’s operations affecting the business as well. The implementation of a change may be considered a project, only of a minor scale. Under that perspective, this work elaborates a methodology for change management under the ITIL framework based on the Project Management’s best practices of the Project Management Institute. The new methodology is based on the analysis of change management on one account currently managed by Hewlett-Packard and the best practices guides of both ITIL and the PMBoK®. The methodology is presented as its constitutive elements, as known, roles and responsibilities, documents and one flow diagram of the process.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Acádemica de Gerencia de Proyectos, 2011.
Keywords: Outsourcing; Herramientas; Información; Gestión de proyectos; Diseño; Tecnología